2018
DOI: 10.1021/acs.macromol.8b00487
|View full text |Cite
|
Sign up to set email alerts
|

Isomannide-Containing Poly(butylene 2,5-furandicarboxylate) Copolyesters via Ring Opening Polymerization

Abstract: Cyclic oligomers of isomannide 2,5-furandicarboxylate were synthesized using the high dilution condensation method. A mixture of dimer, trimer and tetramer species largely enriched in the dimer was obtained. These cyclic oligomers were copolymerized with those made of butylene 2,5-furandicarboxylate in bulk at 220 º C by ring opening polymerization using Sn(Oct) 2 as catalyst. A series of random poly(butylene 2,5-furandicarboxylate) copolyesters containing isomannide in a range of 5 to 50 %-mole and with weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 53 publications
(131 reference statements)
1
32
0
Order By: Relevance
“…The vast majority of these copolymers were prepared by melt polycondensation reactions at high temperatures. A number of alternative approaches has also been investigated; the synthesis of cyclic furanoate oligomers has allowed for the preparation of furanoate copolymers, notably PBF copolymers, by ring-opening polymerization (ROP) [ 64 , 66 , 83 , 86 , 98 , 105 ]. Additionally, the use of enzymatic polymerization has been employed, which warrants a more sustainable synthetic procedure and milder reaction conditions [ 80 , 86 , 93 ].…”
Section: Synthesis Molecular Weight and Randomness Of Fdca-basedmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of these copolymers were prepared by melt polycondensation reactions at high temperatures. A number of alternative approaches has also been investigated; the synthesis of cyclic furanoate oligomers has allowed for the preparation of furanoate copolymers, notably PBF copolymers, by ring-opening polymerization (ROP) [ 64 , 66 , 83 , 86 , 98 , 105 ]. Additionally, the use of enzymatic polymerization has been employed, which warrants a more sustainable synthetic procedure and milder reaction conditions [ 80 , 86 , 93 ].…”
Section: Synthesis Molecular Weight and Randomness Of Fdca-basedmentioning
confidence: 99%
“…The research group of Dr. Muñoz-Guerra has synthesized various furanoate-containing cyclic oligomers (mixtures of dimers, trimers, and tetramers mainly) and copolymerized them by entropically-driven ROP ( Scheme 2 ) [ 64 , 66 , 69 , 83 , 86 , 105 ]. One of the advantages of ROP is the high polymerization rate, which results in relatively milder conditions and shorter reaction times compared to traditional two-step melt polycondensations.…”
Section: Synthesis Molecular Weight and Randomness Of Fdca-basedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the oxy-heterocyclic FDCA molecule exhibits a higher hydrophilicity than terephthalic acid, PBF homopolyester remains highly resistant to biodegradation under natural environmental conditions or lipase-catalyzed conditions (37°C, pH 7.4). 35 Our previous study regarding the (bio)degradability of terephthalic acid-based copolyesters showed that the presence of IS moieties enhances the hydrolytic degradation of the polymers to a certain extent, yet insignificantly influences their biodegradation properties. 23 For PBIF copolyesters, the crystallinities are much inhibited which, together with the high hydrophilicity of the materials, might result in degradable polyesters with enhanced thermal properties.…”
Section: Degradability Of Copolyestersmentioning
confidence: 99%